Strike a pose : eccentric architecture and spectacular spaces. - Klanten, Robert, 1964-; Feireiss, Lukas, ....- (Berlijn : Gestalten, 2008)
Strike a Pose documents a new extroverted architectural language. Manifested in spectacular structures, eccentric forms and vivid colours, this expressive approach goes way beyond conventional stylistic and geographic boundaries. Strike a Pose leads the reader around the globe to iconographically charged scenes and futuristic spaces, with examples of architectural playfulness and experimental wanderlust ranging from private residences to schools and operas, museums and interior design.
Keywords: Fantastische architectuur